Optimizing entrepreneurial development processes for smart specialization in the European Union - Szerb, László; Ortega‐Argilés, Raquel; Acs, Zoltan J.; Komlósi, Éva (Papers in regional science, 2020)
This paper demonstrates how the Regional Entrepreneurship and Development Index (REDI) can be used to optimize local entrepreneurial discovery processes, in a manner which can support smart specialization strategies (S3). While S3 industry prioritization is based on the identification of local strengths, regional improvement can be achieved by improving the weakest features of the local entrepreneurial ecosystem. REDI based suggestions are place‐based and offer rationale for tailor‐made regional policy interventions. We found that without optimizing the entrepreneurial ecosystem, the industry specialization alone may not be successful because of the inability of the ecosystem to nurture high growth ventures. Resumen Este artículo demuestra que el Índice de Desarrollo e Iniciativa Empresarial Regional (IDIE) se puede utilizar para optimizar los procesos de descubrimiento de iniciativas empresariales locales, de manera que pueda servir de apoyo a las estrategias de especialización inteligentes (S3, por sus siglas en inglés). Si bien la priorización de industrias de las S3 se basa en la identificación de las fortalezas locales, la mejora regional se puede lograr mejorando las características más débiles del ecosistema local de iniciativas empresariales. Las sugerencias basadas en el IDIE están ligadas a cada lugar y ofrecen una justificación para realizar intervenciones formuladas a medida para las políticas regionales. Se descubrió que si no se optimiza el ecosistema de iniciativas empresariales, la especialización de la industria por sí sola puede no tener éxito, debido a la incapacidad del ecosistema para fomentar empresas de alto crecimiento. 抄録 本稿では、スマート・スペシャリゼーション戦略(smart specialization strategies:S3)を支持する方法で、地域の起業家的発見のプロセスを最適化するために、Regional Entrepreneurship and Development Index (REDI:地域のアントレプレナーシップと発展の指数)をどのように利用することができるかを例示する。S3は地域の強みを特定することにより産業の優先順位付けを行っているものの、地域の改善は、地域の起業エコシステムの最たる弱点を改善して達成できるものである。REDIに基づく提案は、地域ベースのものであり、地域個別の地域政策の介入の根拠を提示するものである。エコシステムには急成長ベンチャーを育成する能力がないため、起業エコシステムの最適化なくしては、産業特化は成功しない可能性があると考えられる。